Design of a charcoal/methanol solar refrigerator - Quagraine, Francis Eku (2012)
A Thesis presented to the School of Engineering, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirement for a Master of Science Degree in Mechanical Engineering.